Effect of third molars in the line of mandibular angle fractures on postoperative complications: systematic review and meta-analysis. Issue 4 (April 2020) - Fernandes, I.A.; Souza, G.M.; Silva de Rezende, V.; Al-Sharani, H.M.; Douglas-de-Oliveira, D.W.; Galvão, E.L.; Falci, S.G.M.
Abstract: The aim of this systematic review was to verify whether the presence of a lower third molar in the mandibular angle fracture line is associated with postoperative complications. An electronic survey was conducted in five databases. Eligibility criteria included observational and experimental studies that evaluated the association between the presence of the lower third molar in the fracture line of mandibular angle fractures and possible postoperative complications, including infection, paresthesia, necessity of plate removal, temporomandibular joint disorders, malocclusion, dehiscence, and non-union. Thirty-four papers were included in the qualitative analysis and 26 of those in the meta-analysis. The risk of bias of observational studies was assessed by Newcastle–Ottawa scale and of the clinical trials by Cochrane Collaboration risk-of-bias tool. Absence of the third molar was associated with a lower chance of postoperative infection in angle fractures compared to presence of the tooth (odds ratio 0.55, 95% confidence interval 0.34–0.88). No statistically significant difference between the groups was found for the other outcomes evaluated. The findings of this systematic review suggest that the absence of the third molar in the mandibular angle fracture line is associated with a lower postoperative infection rate when compared to angle fractures with a third molar present.